The Gestalt Pedagogical Method as a Path to Better Mental Health - VODIČAR, Janez (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2025)
Gestalt pedagogy takes an anthropological starting point: the here and now. We use the example from the Gospel of John (8:1-11); it was Jesus' withdrawal that enabled the crowd to embark on the path of healing. Using the students' experiences and Paul Ricoeur's hermeneutic approach, we show how he uses the process of distancing in his hermeneutics. This dimension of Gestalt and the hermeneutic process enable a healthy interaction between figure and ground in the complexity of life as understood by Gestalt psychology. The narrative used by the regular methodological approach in Gestalt pedagogy and Christian proclamation is used to show the need for distance. In this way we create a fruitful hermeneutic process that incorporates a meaningful distance for a more effective pedagogical and therapeutic process. Above all, such a distancing process with a suitable method enables the individual to act more and more independently in everyday situations. It is precisely the religious dimension that makes it possible to step out of the here and now in order to strengthen the sources of resources for life.